The Hybridization of Meaningful Nonprofit Work: An Exploratory Study of the Effects of Marketization on Nonprofit Managers' Sense of Meaningfulness in Work. (June 2022) - Sandberg, Billie; Robichau, Robbie Waters
Nonprofit work is oftentimes viewed as inherently meaningful work, but the world of nonprofit work is changing by becoming increasingly marketized. These changes are impacting nonprofit workers' conception and experience of meaningful work. Drawing from scholarship on neoliberal marketization, enterprise culture, and meaningful nonprofit work, this exploratory study examines how an increasingly marketized work environment is influencing nonprofit managers' experience of meaningful work. Findings from interviews demonstrate that nonprofit managers conceive of and experience meaningful work in expected ways (e.g., through serving others). At the same time, findings indicate that their experience of meaningful work evokes elements of enterprise culture. These findings suggest that meaningful nonprofit work is becoming hybridized such that it evokes both prosocial and neoliberal market values. This in turn necessitates a reconsideration of the motivations of nonprofit workers as well as our understanding of the mechanisms by which the nonprofit sector is becoming marketized.